An Assessment of Consumer Awareness and Coverage of Digital Television Services in Uganda (British Journal of Multidisciplinary and Advanced Studies, 2023)
The research examined the relationship between consumer awareness and coverage of digital TV services in Uganda. The study utilised an appropriate study design help gather data. survey tools and interviews guides helped gather information from people who owned television sets. Analysis of data involved describing, correlations and regressions. Research findings concludes consumer awareness predicts Coverage of Digital TV Services. It is recommended that there is need for revision of the current policy objective 4 a) so that it can cater for new media like social media to promote consumer awareness. The means of disseminating consumer awareness need to be diversified. Government should compel all content providers to create space in their programming for consumer awareness.